Predictive Power of Candlestick in Malaysia: Reversal versus Continuation Patterns - Chee, Ling Chin; Mohamad, Jais; Sophee Sulong, Balia (Universiti Malaysia Sarawak (UNIMAS), 2018)
The practice of technical analysis which utilizes past market information to predict future market movement is typically rejected by weak form market efficiency. Despite that, investors often apply technical indicators to enhance trading profits, especially through the Japanese candlestick charting technique. The current study intends to investigate the effectiveness of candlestick charting in Malaysian stock market by comparing between the reversal and continuation patterns within the sample period of 2000 to 2014. After taking into account the transaction costs, the findings show that reversal patterns are more effective than continuation patterns in portraying accurate trading signals particularly for the bearish reversal patterns. Besides, a 15-day holding period is identified to be appropriate for trading in the Malaysian stock market apart from the 10-day maximum holding period.